Candidacidal effect of Moringa stabilized silver nanomaterials reveal disruption of cell wall integrity, efflux pump, vacuole homeostasis and virulence traits in Candida auris - Insha Nahvi; Suriya Rehman; Ankush Kaushik; B. Rabindran Jermy; Sultan Akhtar; Mohd Farhan; Zeeshan Fatima; Saif Hameed (PLoS ONE, 2025)
Candida auris ( C. auris ) is known as a superbug characterized by its high prevalence of multi-drug resistance, causing outbreaks in healthcare settings and leading to high mortality rates worldwide. Developing novel and efficient measures to combat its spread and mitigate its impact on patient outcomes is pertinent. This study describes a simple and eco-friendly method for synthesizing silver nanocomposites and silver-zinc nanocomposites using leaf extract of the Moringa Oleifera (MO), plant. The synthesized nanocomposite was characterized and confirmed by several techniques like Fourier Transform Infrared Spectroscopy (FTIR), X-ray diffractometry (XRD), Thermogravimetric Analysis (TGA), X-ray Photoelectron Spectroscopy (XPS), Scanning electron microscopy (SEM). Moreover, nanocomposites were observed to display effective action against C. auris. Minimum inhibitory concentration (MIC) of Ag- MO and Ag-Zn- MO nanocomposite was found to be 125 µg/mL and 250 µg/mL respectively. Ag- MO was found to be fungicidal in nature while Ag-Zn- MO was fungistatic at their respective MIC’s. Mechanistic insights elucidate changed cell wall composition, impaired efflux activity, dysfunctional vacuole and suppressed biofilm formation. In vivo efficacy was demonstrated via nematode model survival and macrophage mediated killing. Both the nanocomposites enhanced Caenorhabditis elegans survival which was 45% in Ag- MO , 41% in Ag-Zn- MO vs. 30% in untreated and also enhanced macrophage mediated killing of C. auris . The current study highlights the potential application of Moringa synthesized AgNPs and Ag-ZnNPs as promising approach to combat C. auris infections in particular post its biocompatibility studies.